Chemical Recruitment for Foraging in Ants (Formicidae) and Termites (Isoptera): A Revealing Comparison - Klaus Jaffe; Solange Issa; Cristina Sainz-Borgo (Psyche: A Journal of Entomology)
All termites secrete trail pheromones from their sternal gland, whereas ants use a variety of glands for this purpose. This and the diversity of chemical compounds that serve as trail pheromones among ants, and the uniformity of chemicals among termite trails, suggest a different evolutionary historical dynamics for the development of chemical mass recruitment in both taxa. Termites in addition show pheromonal parsimony. This suggest a single evolutionary origin of pheromone trails in Isoptera, whereas chemical mass recruitment among Formicidae seems to have evolved many times and in different ways. Despite these very different evolutionary histories, both taxa evolved chemical recruitment systems involving attractants and orientation signals, and at least two divergent decision making system for recruitment. This evolutionary analogy suggests that chemical mass recruitment is constraint by fundamental physical dynamic laws. Artificial intelligence including “mass intelligence” and “ant intelligence”, emulates mass recruitment in interacting virtual agents in search of optimal solutions. This approach, however, has copied only the “Democratic” recruitment dynamics with a single compound pheromone. Ant and termite evolution shows more sophisticated recruitment dynamics which, if understood properly, will improve our understanding of nature and applications of artificial “swarm intelligence”.